Increased human herpesvirus-8 neutralizing response during remission from Kaposi’s sarcoma - Byren, Hannah; Holzer, Angela; Müller, Alexander; Korn, Klaus; Backovic, Marija; Harrer, Ellen; Bergmann, Silke; Harrer, Thomas; Neipel, Frank (Journal of General Virology, 2024)
Human herpesvirus-8 (HHV-8), also known as Kaposi’s sarcoma-associated herpesvirus, is a human oncogenic herpesvirus that is responsible for several diseases including Kaposi’s sarcoma (KS). KS prevalence varies dramatically, although emergence increases considerably with human immunodeficiency virus -1 (HIV-1) co-infection, making it one of the most common cancers in HIV-1 patients and sub-Saharan African men, even prior to the HIV-1 epidemic in Africa. Studies have shown that neutralizing antibodies exist in HHV-8-infected sera, which are most likely targeted to viral lytic surface glycoproteins, such as glycoprotein K8.1 (gpK8.1) and gHgL. Fifty-eight HHV-8-positive serum samples were tested for the levels of gpK8.1- and gHgL-binding antibodies and in vitro HHV-8-neutralizing capacity. Each sample was then categorized according to the disease status, which included asymptomatic infection, active KS and remission from KS, and the three measured parameters were compared between the disease groups. We show that neutralizing capacity in infected patient sera increases with remission of KS. Interestingly, antibodies targeting gpK8.1, but not gHgL, were also found to be increased during active disease and remission. Comparison of neutralizing capacity and antibody levels on an individual patient basis revealed that antibody levels, primarily targeting gHgL, are correlated with serum neutralizing response in sub-lingual Kaposi sarcoma (SLK) cells. Adsorption of gHgL or gpK8.1 antibodies from human sera removed the neutralizing response in SLK cells, although some non-specific removal of antibodies from the sera means that this result should be interpreted with caution. Taken collectively, these results suggest that glycoproteins, such as gHgL, are targets for neutralizing antibodies. Furthermore, our data imply that recovery from KS is associated with increased neutralizing capacity, suggesting that neutralizing antibodies may contribute to KS resolution. However, it is vital for further work to be completed in order to elucidate this relationship.
CRIS-Team Scopus Importer:2024-12-13
Keywords: gHgL; gpk8.1; HHV-8; Kaposi's sarcoma; neutralizing antibodies; remission